Study of micro flexible rolling based on grained inhomogeneity. (April 2017) - Qu, Feijun; Jiang, Zhengyi; Wei, Dongbin; Chen, Qingqiang; Lu, Haina
Abstract: This paper shows an analytical, numerical and experimental investigation to comprehend the role of grained inhomogeneity which plays in micro flexible rolling in terms of the average rolling force and the thickness directional springback of the workpiece after it exits the roll bite zone. Miniature tensile tests and micro hardness tests are accomplished to identify the scattered stress-strain curves for 500 μm thick aluminium alloy 1060 samples with grain size of approximately 23-71 µm and to determine the weighted heterogeneity coefficient for each sample separately, according to which the theoretical calculations and numerical simulations based upon 3D Voronoi tessellation technique have been performed under actual experimental conditions where reductions of 25 to 50 % are selected. The scattering effect associated with the anisotropic nature of single grains has been perceived in the micro flexible rolling process and both the analytical and finite element models developed have been validated via experimental data to hold promise for predicting the rolling force and the thickness directional springback of the workpiece, as well as boosting the thickness profile control performance of the micro flexible rolling mill. Graphical abstract: Highlights: 2D models are created for flexible rolling of submillimeter thick strips. Scatter effect of flow stresses of the materials is identified and expounded. 3D Voronoi tessellation is used to mimic the crystalline structure of materials. The grained heterogeneity is revealed both numerically and experimentally. The developed numerical and analytical models are validated with measured data.